Effects of job stressor on psychological well- being among the nurses at hospital during pandemic covid-19 - Anthony, P.M; Aren, Merikan; Rekayasa, Vincent Balang (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2021)
As a result of the recent pandemic, the psychological wellbeing among nurses can be overlooked despite anecdotally it has greatly affect nurses’ wellbeing. Hence, this study aimed to identify the effects of job stressors on the psychological wellbeing among nurse in the hospital during pandemic COVID-19. This study also to identify the effects of job stressors on the autonomy, environmental mastery, personal growth, positive relations with others, purpose in life, self-acceptance among the nurses. Random sampling was used to select 128 nurses were who were working in the hospital were randomly selected. The respondents were asked to complete a questionnaire using Google Form via online. The Work Stress Scale and Ryff’s Psychological Well-Being Scale (PWBS) were used to test the hypotheses of the study. The dataset was analysed by using Statistical Package for The Social Sciences (SPSS), Version 25. The result showed that there were significant negative effects of job stressors on psychological wellbeing. The results also indicated that the job stressors have positive impact on autonomy and self-acceptance among nurses. Hence, the stakeholder should take appropriate and effective measures to minimize the impact of job stressors and increase the level of psychological wellbeing among nurses. The findings of the study have reflected an important and beneficial implication to the health care sector of Malaysia in producing more capable nurses and ready to face any challenge during pandemic.